Práticas em Docência em Biologia: Ideias Simples e Inovadoras - Silveira, Jader Luís da (2021)
The discipline of Biology is an indispensable discipline for learning. It is endowed with theories and a complex vocabulary. For better use and absorption, it is necessary to make use of several different and fun ways to involve and increase the interest of students, combining theory and practice. Theory is indispensable, however, if it is complemented by practical classes, the quality of teaching increases and its content fixation as well. The practical class makes the student participate directly in each process, contributing to the construction of the discipline, in addition to strengthening ties between student and teacher, allowing for teaching that goes beyond the conventional, looking for new alternatives. Thus, developing with the students, the ability to work in groups, thus obtaining greater benefit for both. The objective of this work is to help teachers and students in the development of their classes and in the search for the construction of a teaching-learning process in a collective and collaborative way, valuing experiences and experiences. Thus, it is expected that the student is, in fact, the protagonist of their learning.